The impact of a mixed reality technology-driven health enhancing physical activity program among community-dwelling older adults: a study protocol - Dino, Michael Joseph S.; Dion, Kenneth W.; Abadir, Peter M.; Budhathoki, Chakra; Huang, Chien-Ming; Padula, William V.; Himmelfarb, Cheryl R. Dennison; Davidson, Patricia M. (Frontiers in Public Health, 2024)
Background. Physical inactivity and a sedentary lifestyle among community-dwelling older adults poses a greater risk for progressive physical and cognitive decline. Mixed reality technology-driven health enhancing physical activities such as the use of virtual coaches provide an emerging and promising solution to support healthy lifestyle, but the impact has not been clearly understood.Methods and analysis. An observational explanatory sequential mixed-method research design was conceptualized to examine the potential impact of a user-preferred mixed reality technology-driven health enhancing physical activity program directed toward purposively selected community-dwelling older adults in two senior centers in the Philippines. Quantitative components of the study will be done through a discreet choice experiment and a quasi-experimental study. A total of 128, or 64 older adults in each center, will be recruited via posters at community senior centers who will undergo additional screening or health records review by a certified gerontologist to ensure safety and proper fit. Treatments (live coaching with video-based exercise and mixed reality technology-driven exercise) will be assigned to each of the two senior center sites for the quasi-experiment. The participants from the experimental group shall be involved in the discreet choice experiment, modeling, and usability evaluations. Finally, a qualitative sample of participants (n=6) as key informants shall be obtained from the experimental group using purposive selection.Discussion. This study protocol will examine the health impact of a promising mixed reality program in health promotion among older adults. The study utilizes a human-centered mixed method research design in technology development and evaluation in the context of developing nations.Trial Registration. This project was retrospectively registered at ClinicalTrials.gov [ID NCT06136468]